Understanding the Needs of Children With Medical Complexity - Kathleen Huth; Sara Long-Gagne; Jessica Mader; Anne Marie Sbrocchi (Association of American Medical Colleges, 2018)
Introduction Children with medical complexity (CMC) are characterized by chronic conditions, functional limitations, technology dependence, and high health care utilization. There are limited formal training opportunities in the provision of complex care for pediatric residents. Methods We developed a module to enable target learners to understand unique needs of CMC and the general pediatrician's role in creating a medical home. The module was piloted in a single pediatric residency program. The 60-minute session incorporated small-group activities and didactic instruction. Learners were given formative pre- and posttest questions to check understanding and completed a 1-minute paper to summarize anticipated changes in practice. Qualitative content analysis was used to identify themes in written responses. Results Fifteen pediatrics residents participated in the module at a single children's hospital. Most residents had not had a complex care clinical rotation. Themes in learner knowledge of CMC included recognizing functional limitations and recurrent health care utilization. Themes from anticipated changes in practice included having less fear/anxiety when approaching care for CMC and asking about diverse areas of need, including nonmedical. Discussion This core module was developed as part of a national systematic approach to complex care curriculum development. It has the potential to be adapted to frame a broader complex care curriculum and to be implemented with other learners in the health professions who care for this vulnerable patient population. The pilot study informed implementation in multiple residency programs, with the goal of enabling future pediatricians to provide high-quality care within a medical home for CMC.